Bilateral isolated concurrent superior ophthalmic vein thrombosis in systemic lupus erythematosus - Sambhav K; Shakir O; Chalam KV (International Medical Case Reports Journal, 2015)
Kumar Sambhav, Omar Shakir, Kakarla V Chalam Department of Ophthalmology, College of Medicine – Jacksonville, University of Florida, Jacksonville, FL, USA Abstract: We describe a case of bilateral consecutive superior ophthalmic vein thrombosis as a presenting feature in a patient previously not known to have systemic lupus erythematosus (SLE). A 68-year-old African–American female presented with decreased vision in right eye, mild right orbital tenderness, and frontotemporal headache of 3 days duration. MRI of the orbits confirmed thrombosis of the right superior ophthalmic vein without extension into the cavernous sinus. Sequential MRI at 1 month showed interval improvement of the right superior ophthalmic vein thrombosis and a new thrombosis in the left superior ophthalmic vein. Renal biopsy revealed granular membranous and mesangial deposits of IgG, IgA, IgM, C3, and C1q and confirmed the diagnosis of SLE. Keywords: superior ophthalmic vein thrombosis, systemic lupus erythematosus, MRI in SOVT